Tackling a Curious Case: Generation of Charge-Tagged Guanosine Radicals by Gas-Phase Electron Transfer and Their Characterization by UV-vis Photodissociation Action Spectroscopy and Theory - Liu, Yue; Ma, Congcong; Leonen, Calvin J A; Chatterjee, Champak; Nováková, Gabriela; Marek, Aleš; Tureček, František (Journal of the American Society for Mass Spectrometry, 2021)
We report the generation of gas-phase riboguanosine radicals that were tagged at ribose with a fixed-charge 6-(trimethylammonium)hexane-1-aminocarbonyl group. The radical generation relied on electron transfer from fluoranthene anion to noncovalent dibenzocrown-ether dication complexes which formed nucleoside cation radicals upon one-electron reduction and crown-ether ligand loss. The cation radicals were characterized by collision-induced dissociation (CID), photodissociation (UVPD), and UV-vis action spectroscopy. Identification of charge-tagged guanosine radicals was challenging because of spontaneous dissociations by loss of a hydrogen atom and guanine that occurred upon storing the ions in the ion trap without further excitation. The loss of H proceeded from an exchangeable position on N-7 in guanine that was established by deuterium labeling and was the lowest energy dissociation of the guanosine radicals according to transition-state energy calculations. Rate constant measurements revealed an inverse isotope effect on the loss of either hydrogen or deuterium with rate constants kH = 0.25-0.26 s-1 and kD = 0.39-0.54 s-1. We used time-dependent density functional theory calculations, including thermal vibronic effects, to predict the absorption spectra of several protomeric radical isomers. The calculated spectra of low-energy N-7-H guanine-radical tautomers closely matched the action spectra. Transition-state-theory calculations of the rate constants for the loss of H-7 and guanine agreed with the experimental rate constants for a narrow range of ion effective temperatures. Our calculations suggest that the observed inverse isotope effect does not arise from the isotope-dependent differences in the transition-state energies. Instead, it may be caused by the dynamics of post-transition-state complexes preceding the product separation.